Does privatization decrease the structural efficiency in the Chinese hospital sector? - Xinju He; Yi Liu (Health Economics Review)
Abstract This paper examines the resource mismatch in China’s healthcare sector from 2010 to 2019. We use structural efficiency to measure the resource mismatch in the healthcare industry (0.2–0.7). We find that an increase in the proportion of private hospitals decreases the healthcare resource mismatch across provincial regions. This ameliorative effect is evident in non-coastal as well as central provinces. In addition, we also find that an increase in the proportion of private hospitals leads to a greater supply of healthcare resources and the number of healthcare services, which in turn better meets the healthcare needs of local residents and decreases the healthcare resource mismatch between regions in each province.